GERAKAN BANK SAMPAH SEKOLAH TINGKAT PENDIDIKAN ANAK USIA DINI DI PAUD TIGA BAHASA NAILUN NABHAN - Muhammad Nawir; Sitti Asnaeni AM; A Nur Achsanuddin UA; St Asriati AM; Sarmila M; Rahmadani Islawiyah M (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2023)
Paud Tiga Bahasa Nailun Nabhan, located at Griya Rezeki Abadi Housing, SmbaOpu Subdistrict, Mawang Village, Gowa Regency. Human behavior that is not disciplined in managing waste needs to be changed. This should be instilled from an early age, that is, since children are kindergarten. So that the formation of clean and healthy living behavior can be formed from an early age, the waste bank movement was launched at Nailun Nabhan Three language Early Childhood Education, then parents transmit the education they have received to their children, assisted by teachears at Paud Tiga Bahasa Nailun Nabhan. The education delivered to parents is about the dangers of littering and the benefits of waste management. The method used is qualitative by providing socialization and providing guidance to parents in the Paud Tiga Bahasa Nailun Nabhan. The results of the waste bank movement are 1) environmental values; 2) social values; 3) economiv value. Â Â